A245 IMPROVING KNOWLEDGE TRANSFER OF PREVENTATIVE CARE IN INFLAMMATORY BOWEL DISEASE USING ELECTRONIC LEARNING. (26th February 2020) - Tandon, P; Sasson, A N; Gallinger, Z
Abstract: Background: Inflammatory bowel disease (IBD) is a complex chronic disease and it is imperative that gastroenterologists are familiar with the unique needs of the IBD patient. An important part of management involves education surrounding the general health maintenance needs of this patient population, especially those on immunomodulator and biologic therapy or those being considered for such treatment. A recent study showed that Canadian GI trainees are uncomfortable managing preventative care in IBD including vaccinations and bone protection. Using educational videos for trainees to improve core knowledge of these concepts remains unclear. Aims: Assess educational efficacy of a core training module on trainee confidence and knowledge on preventative care in IBD. Methods: This study assessed a preventative care in IBD video used as an educational tool in the University of Toronto GI trainee program as part of the annual GI in-training objective structured clinical examination (OSCE). Prior to the OSCE, a randomly selected cohort of trainees were provided the preventative care video. The remaining trainees prepared for the OSCE as standard. At the OSCE, one station asked all trainees to address preventative care in IBD with a standardized patient. Following the OSCE, a standardized evaluation of trainee confidence and degree of knowledge on vaccination, cancer screening, bone health, and mental health in IBD patients was performed. These evaluations and OSCE score were then compared between both cohorts. Data was analyzed using a t-test and p<0.05 was considered significant. Results: A total of 10 subjects took part in the study. 5 subjects were exposed to the video prior to the OSCE and 5 were not exposed. Overall total score for trainees who had seen the video prior to the OSCE had a mean score of 85.3% (38.4/45) compared to those who had not seen the video prior had a mean score of 65.3% (29.4/45) with a p = 0.03. Global score in those exposed to the video was 70% (3.5/5) compared to 48% (2.4/5) in the unexposed group with a p= 0.006. Upon assessment of individuals topics, there was a trend in improved knowledge of vaccination and mental health screening in those exposed vs. unexposed to the educational video (52.6% vs. 32.6%, and 80% vs. 20%, respectively). No significant difference was identified between groups with respect to cancer screening and bone health. Conclusions: Our study shows evidence that use of educational videos was efficacious with respect to GI trainee confidence and knowledge surrounding key concepts in preventative care of IBD patients. This exposure allows for improved patient education and management and lead to better-quality patient care. Overall, this study identifies a knowledge gap in trainee education and highlights the need for development of training tools to improve overall management of this complex and dynamic disease. Funding Agencies: CAGVideo was a CAG accredited educational material, and supported by an educational grant from the Canadian Association of Gastroenterology and Abbvie Canada